Epidural Space Identification With Loss of Resistance Technique for Epidural Analgesia During Labor: A Randomized Controlled Study Using Air or Saline—New Arguments for an Old Controversy. (February 2018) - Brogly, Nicolas; Guasch, Emilia; Alsina, Estibaliz; García, Carla; Puertas, Laura; Dominguez, Ana; Diez, Jesús; Gómez, Jorge; Gilsanz, Fernando
Abstract : BACKGROUND: The best technique to identify the epidural space for labor analgesia is still unclear despite the publication of various randomized controlled studies and meta-analyses. Our aim was to assess the superiority of the saline loss of resistance (SLOR) technique over the air loss of resistance (ALOR) technique with respect to the quality of the block. METHODS: Consenting parturients admitted to our obstetric suite for spontaneous or induced labor were randomized to receive epidural analgesia using either the ALOR or SLOR technique. Our primary outcome was to compare the impact of the SLOR and ALOR technique on pain score improvement measured 30 minutes after administration of epidural block. Our secondary outcomes included the density of motor blockade and analgesic efficacy measured at 30 minutes. Primary and secondary outcomes were compared using the Student t test and Mann-Whitney U test. Statistical significance was set at P < .017 for primary and secondary outcomes, considering Bonferroni correction for multiple comparisons. Other comparisons were considered exploratory. RESULTS: Four hundred parturients were included; 24 were excluded from the final analysis. After 30 minutes, pain score reduction (ALOR, 4.7 ± 2.9/10; SLOR, 4.9 ± 3.0/10; P = .49), motor block (ALOR, 1.4 ± 0.8; SLOR, 1.3 ± 0.8; P = .27), and efficacy of the block (ALOR, 1.0 ± 0.7; SLOR, 1.0 ± 0.6; P = .87) did not differ significantly between groups. CONCLUSIONS: Pain score reduction after 30 minutes and onset of the block were not affected by the technique used to locate the epidural space. Abstract : Published ahead of print November 14, 2017.